CD27+CD38hi B Cell Frequency During Remission Predicts Relapsing Disease in Granulomatosis With Polyangiitis Patients - von Borstel, Anouk; Land, Judith; Abdulahad, Wayel H.; Rutgers, Abraham; Stegeman, Coen A.; Diepstra, Arjan; Heeringa, Peter; Sanders, Jan Stephan (Frontiers in Immunology, 2019)
Background Granulomatosis with polyangiitis (GPA) patients are prone to disease relapses. We aimed to determine whether GPA patients at risk for relapse can be identified by differences in B cell subset frequencies. Methods Eighty-five GPA patients were monitored for a median period of 3.1 years (range: 0.1-6.3). Circulating B cell subset frequencies were analyzed by flow cytometry determining expression of CD19, CD38 and CD27. B cell subset frequencies at time of inclusion of future-relapsing (F-R) and non-relapsing (N-R) patients were compared and related to relapse-free survival. Additionally, CD27+CD38hi B cells were assessed in urine and kidney biopsies from active anti-neutrophil cytoplasmic autoantibody-associated vasculitides (AAV) patients with renal involvement. Results Within 1.6 years, 30% of patients experienced a relapse. The CD27+CD38hi B-cell frequency at the time of inclusion was increased in F-R (median: 2.39%) compared to N-R patients (median: 1.03%; p=0.0025) and a trend was found compared with the HCs (median: 1.33%; p=0.08). This increased CD27+CD38hi B cell frequency at inclusion was correlated to decreased relapse-free survival in GPA patients. In addition, 74.7% of patients with an increased CD27+CD38hi B cell frequency ( 2.39%) relapsed during follow-up compared to 19.7% of patients with a CD27+CD38hi B cell frequency of <2.39%. No correlations were found between CD27+CD38hi B cells and ANCA levels. CD27+CD38hi B cell frequencies were increased in urine compared to the circulation, and were also detected in kidney biopsies, which may indicate CD27+CD38hi B cell migration during active disease. Conclusions Our data suggests that having an increased frequency of circulating CD27+CD38hi B cells during remission is related to a higher relapse risk in GPA patients, and therefore might be a potential marker to identify those GPA patients at risk for relapse.